RENDEMEN PENGOLAHAN FINIR KAYU KERUING (Dipterocarpus spp) PADA KELAS DIAMETER DAN MESIN ROTARY BERBEDA DI PT. KORINDO ARIABIMA SARI PANGKALAN BUN - Novitasari Novitasari; Zainal Abidin; Lusyiani Lusyiani (Jurnal Sylva Scienteae, 2020)
Rotary is a machine that can converts pieces of wood logs into finir sheets then made into plywood so that rotary machine have the potential to produce waste in the processing of plywood. Rotary machines are used with two types of determination of different midpoints by determining the midpoint with photo camera switches and projector lights. The purpose of this study is to analyze the differences between the tools that was used against the rendement that had been produced and analyze the differences of diameter classes along the production process. This research was conducted at the plywood manufacturing company PT. Korindo Ariabima Sari Pangkalan Bun. The method was used by conducting observations and recording the results of the research, the experimental design pattern that had been used is completely randomized design (CRD). The results of this study indicate the difference in the tools that had been used (factor A) by using a photo switch camera, the result of the rendement is greater (about 72.971%)  compared with projector lamp which produces a smaller percentage of the rendement (about 69.870%), the difference in diameter class (factor B), greater rendement is produced in the class diameter of 60-69 cm with a value of 76,248% and smaller rendement are produced in the class diameter of 90-99 cm with a value of 68,175%.Keywords: Projector Lamp; Plywood; Rotary Machine; Rendement